USE OF ENTERPRISE RESOURCE PLANNING (ERP) SYSTEM IN CHINESE SMALL AND MEDIUM ENTERPRISES (SMES) - Qing Ren; Saichon Pinmanee; Singha Chaveesuk (Operational Research in Engineering Sciences: Theory and Applications)
Major organizations are maturing and have extensively used Enterprise Resource Planning (ERP) System systems. However, due to intense rivalry, China's small and medium enterprises (SMEs) have not yet implemented ERP systems. Therefore, the study aimed to test a model for the use of ERP System in Chinese SMEs. Using cross-sectional research design and purposive sampling technique data were collected from 660 Chinese SMEs ERP users. The SEM analysis results show that organizational, environmental, and service quality factors have a positive and significant impact on ERP usage in Chinese SMEs, while system and information quality also positively influence both ERP usage and user satisfaction. Task-technology fit, driven by task characteristics, has a positive effect on ERP usage, and human self-efficacy contributes positively to both ERP usage and user satisfaction. Additionally, ERP usage and user satisfaction both have a positive and significant impact on SME performance. These findings suggested that SMEs in China should focus on the enhancement of ERP-related factors to increase ERP adoption. Additionally, improving system and information quality, alongside fostering user confidence, can significantly enhance both ERP usage and performance.